PENERAPAN STRATEGI PETA KONSEP UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD MUHAMMADIYAH 6 PEKANBARU - Midun, Muhamad; Marhadi, Hendri; Antosa, Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The background of this study is the low learning achievement of social science of fourth grade students of Muhammadiyah 6 Elementary School Pekanbaru. The mean daily test scores obtained from 24 students was 68. This value is far from the Minimum Passing Score (MPS) of this school which it was 76. This study aims to improve the learning achievements of social science students of fourth grade Muhammadiyah 6 Elementary School Pekanbaru through mapping concept strategy. The type of this study is a classroom action study. The study was conducted in Muhammadiyah 6 Elementary School Pekanbaru with 24 students of fourth grade of that school as the sample. This study showed the teacher activities in every meeting had been increased, for the first cycle was 71,3% and increasing in cycle II become 88%. Student activities were also increased during each meeting, this can be proven by the average of activity of student at cycle I 63% rose to 83,5% in student activity cycle II. Based on the scores of student learning achievements in classical there is an increase in the number of students who reach MPS was on the first cycle percentage of 66.67% while in cycle II the percentage of students' classical completeness was 83%. Implementation of mapping concept strategy could improve student learning result of fourth grade of SD Muhammadiyah 6 Pekanbaru, it can be seen from the average score of base is 68,21 in cycle I increased to 74,58 with increase of 66,67%, then on cycle II average The primary score score 68.21 was increased to 81.85 with percentage 87.5%.Keywords: mapping concept strategy, learning achievements